Sosialisasi Pentingnya Cuci Tangan 6 Langkah Pada Anak - Anak Di Desa Lamteube Geupula Aceh Besar - Yadi Putra; Syukriadi Syukriadi; Fauziah Fauziah (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
Washing hands 6 steps is one way that can be used to overcome disease problems such as diarrhea or intestinal worms. This community service activity aims to increase the knowledge of children in Village Lamteube Geupula in carrying out hand washing. The socialization method is carried out by counseling and demonstrations, this activity is carried out for approximately 2 hours and evaluation. The results obtained from this community service are changes in children's knowledge about 6-step hand washing. This community service activity was carried out on June 27 2023 in the village multipurpose hall, at 10.00 WIB until it finished at 11.40 WIB. Intervention activities were carried out by lecturers and students. Activities carried out directly with counseling and demonstrations. The target of community service activities is 26 children in Village Lamteube Geupula.